"I Still Feel Like I Am Not Normal": A Review of the Role of Stigma and Stigmatization Among Female Survivors of Child Sexual Abuse, Sexual Assault, and Intimate Partner Violence. (December 2018) - Kennedy, Angie C.; Prock, Kristen A.
Child sexual abuse (CSA), sexual assault (SA), and intimate partner violence (IPV) occur within social contexts that shape how survivors judge themselves and are evaluated by others. Because these are gendered sexual and intimate crimes that violate social norms about what is appropriate and acceptable, survivors may experience stigma that includes victim-blaming messages from the broader society as well as specific stigmatizing reactions from others in response to disclosure; this stigmatization can be internalized among survivors as self-blame, shame, and anticipatory stigma. Stigma and stigmatization play an important role in shaping survivors' thoughts, feelings, and behaviors as they recover; their risk of revictimization; and their help-seeking and attainment process. In this review, we synthesize recent CSA, SA, and IPV research ( N = 123) that examines female survivors' self-blame, shame, internalized stigma, and anticipatory stigma as well as negative social reactions in response to survivors' disclosure. We highlight critical findings as well as implications for research, practice, and policy, and we note gaps in our current knowledge.